Ethanol and acetaldehyde potentiate the clastogenicity of ultraviolet light, methyl methanesulfonate, mitomycin C and bleomycin in Chinese hamster ovary cells - Lin, Ying-Chun; Ho, I-Ching; Lee, Te-Chang (Mutation Research/Environmental Mutagenesis and Related Subjects, 1989)
Ethanol itself did not induce any apparent chromosome aberrations in Chinese hamster ovary cells. However, posttreatment with ethanol potentiated the chromosome aberrations induced by ultraviolet light (UV), methyl methanesulfonate (MMS), mitomycin C (MMC) or bleomycin (BLM). Chromatid exchanges were predominantly increased in cultures treated with UV, MMS or MMC and then with ethanol, whereas chromosome breaks and chromatid exchange were the major types of aberrations increased in the cultures treated with BLM and ethanol. Posttreatment with acetaldehyde, the major metabolite of ethanol, also potentiated the chromosome aberrations induced by UV, MMS, MMC or BLM. The main types of aberrations potentiated by posttreatment with acetaldehyde were similar to those by posttreatment with ethanol.